2022
DOI: 10.1021/acs.chemrev.1c00750
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biomolecular Strategies for STING Pathway Activation in Cancer Immunotherapy

Abstract: The stimulator of interferon genes (STING) cellular signaling pathway is a promising target for cancer immunotherapy. Activation of the intracellular STING protein triggers the production of a multifaceted array of immunostimulatory molecules, which, in the proper context, can drive dendritic cell maturation, antitumor macrophage polarization, T cell priming and activation, natural killer cell activation, vascular reprogramming, and/or cancer cell death, resulting in immune-mediated tumor elimination and gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 561 publications
1
103
0
1
Order By: Relevance
“… 123 IFN-β largely depends on the facilitation effect of the enhanceosome and canonical NF-κB can work in conjunction with IRF-3 as well as other enhancer components to maximize the expression of IFN-β gene. 124 , 125 Abe et al observed a 50% decrease in IFN-β production in primary mouse embryonic fibroblast cells when canonical NF-κB expression was partially silenced via RNA interference (RNAi). 119 Similarly, canonical NF-κB and IRF3 are essential to induce type I IFN in DCs stimulated by irradiated tumor cell after IR.…”
Section: Rationale Of Irtmentioning
confidence: 99%
“… 123 IFN-β largely depends on the facilitation effect of the enhanceosome and canonical NF-κB can work in conjunction with IRF-3 as well as other enhancer components to maximize the expression of IFN-β gene. 124 , 125 Abe et al observed a 50% decrease in IFN-β production in primary mouse embryonic fibroblast cells when canonical NF-κB expression was partially silenced via RNA interference (RNAi). 119 Similarly, canonical NF-κB and IRF3 are essential to induce type I IFN in DCs stimulated by irradiated tumor cell after IR.…”
Section: Rationale Of Irtmentioning
confidence: 99%
“…However, 5,6-dimethylxanthenone-4-acetic acid does not activate human STING. Many different CDNs with agonist activity on human STING have been developed and are being evaluated as primary or adjunctive therapy in human cancers (reviewed in refs 8 , 9 ). Unsurprisingly, CDNs have also been used to enhance inflammatory responses and reduce SARS-CoV-2 infection of human bronchial epithelial cells in vitro and mouse cells in vivo 157 .…”
Section: Modulation Of Cgas–sting In Diseasementioning
confidence: 99%
“…For example, activation of cGAS–STING, predominantly by mitochondrial DNA (mtDNA), has been implicated in both acute and chronic kidney disease (CKD) 4 7 . However, deep knowledge of the biochemistry of the cGAS–STING cassette has also enabled investigators to harness this pathway to augment immune responses against tumours and reverse cancer-associated immune suppression (reviewed in refs 8 , 9 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…4a–c). 16,17,161 For instance, Weissleder et al used β-cyclodextrin nanoparticles to deliver TLR agonists and thus promote macrophage repolarisation. 162 The authors reported that, compared with other molecules tested (CSF1R inhibitor, tyrosine kinase inhibitor, and other TLR7/8 agonists), resiquimod (R848) (Fig.…”
Section: Chemical Strategies For Modulating the Tmementioning
confidence: 99%